PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PERUSAHAAN DAERAH AIR MINUM (PDAM) TIRTA MUSI PALEMBANG - Sugiri Dinah (JURNAL KOMPETITIF, 2014)
ABSTRAKÃ‚Â .This research was carried out by quantitative analysis approach , the study variable quality of service ( independent variable ) and customer satisfaction ( dependent variable ) . Data were obtained through questionnaires distributed to customers PDAM Tirta Musi Palembang , and library research . Sampling was conducted using a sample region or area probability sample . This research instrument using deferensial Scale Semantics and analysis of data in this study were univariate , bivariate analysis using Chi-square and multivariate analysis using the Multiple Logistic Regression .From the results of this research is that of the 100 respondents who gave ratings are not satisfied by 43 people ( 43 % ) and there were 46 people ( 46 % ) who give bad ratings to the quality of service . There is a significant relationship between the dimensions of tangibles, reliability , and responsivness to customer satisfaction as its p value < ÃŽÂ± ( 0.05 ) and was not a significant difference between assurance and empathy towards customer satisfaction as its p - value > ÃŽÂ± ( 0 , 05 ) . Responsiveness dimension is the dimension of service quality the most influence on customer satisfaction .It is suggested that excellent service quality should be improved by the General Board of the State -wned enterprises in particular taps as water processing , with the goal of satisfying the customer as the result of research that states there is a significant effect of service quality on customer satisfactionÃ‚Â Keywords : Customer Satisfaction, Quality of ServiceÃ‚Â  Ã‚Â